Biodiversity, ecosystems, and conservation in northern Mexico - Cartron, Jean-Luc E.; Ceballos, Gerardo; Felger, Richard Stephen (Oxford University Press, 2005)
Encompassing tropical and temperate forests, arid lands, and the Gulf of California, northern Mexico is one of the most biologically diverse areas in the world. Representing the collaborative efforts of ecologists in the U.S.